Treatment of spinal anaesthesia-induced hypotension with cafedrine/theodrenaline versus ephedrine during caesarean section: Results from HYPOTENS, a national, multicentre, prospective, noninterventional study. Issue 10 (October 2021) - Kranke, Peter; Geldner, Götz; Kienbaum, Peter; Gerbershagen, Hans Jürgen; Chappell, Daniel; Wallenborn, Jan; Huljic, Susanne; Koch, Tilo; Keller, Thomas; Weber, Stephan; Kunitz, Oliver; Linstedt, Ulf; et al.
Abstract : BACKGROUND: In Germany, hypotension induced by spinal anaesthesia is commonly treated with a combination of cafedrine hydrochloride (C, 200 mg) and theodrenaline hydrochloride (T, 10 mg) in 2 ml. We compared the effectiveness of C/T with ephedrine. OBJECTIVES: The primary objectives were to assess the speed of onset and the ability to restore blood pressure without an increase in heart rate. Secondary objectives were to evaluate maternal/foetal outcomes and the number of required additional boluses or other additional measures. DESIGN: HYPOTENS was a national, multicentre, prospective, open-label, two-armed, noninterventional study comparing C/T with ephedrine in two prospectively defined cohorts. This study relates to the cohort of patients receiving spinal anaesthesia for caesarean section. SETTING: German hospitals using either C/T or ephedrine in their routine clinical practice. PATIENTS: Women aged at least 18 years receiving spinal anaesthesia for caesarean section. INTERVENTIONS: Bolus administration of C/T or ephedrine at the discretion of the attending anaesthesiologist. MAIN OUTCOME MEASURES: Endpoints within 15 min after initial administration of C/T or ephedrine were area under the curve between the observed SBP and the minimum target SBP; and incidence of newly occurring heart rate of at least 100 beats min −1 . RESULTS: Although effective blood pressure stabilisation was achieved with both treatments, this effect was faster and more pronounced with C/T ( P < 0.0001). The incidence of tachycardia and changes in heart rate were higher with ephedrine ( P < 0.01). Fewer additional boluses ( P < 0.01) were required with C/T. Although favourable neonatal outcomes were reported in both groups, base deficit and lactate values were greater with ephedrine ( P < 0.01). Physician satisfaction was higher with C/T. CONCLUSIONS: After C/T, tachycardia was not a problem, providing an advantage over ephedrine. Fewer additional boluses were required with C/T, suggesting greater effectiveness. An increased base deficit with ephedrine suggests reduced oxygen supply or increased demands in foetal circulation. TRIALS REGISTRATION: Clinicaltrials.gov: NCT02893241, German Clinical Trials Register: DRKS00010740. Abstract : Supplemental Digital Content is available in the text